Revealing the complexity of ultra-soft hydrogel re-swelling inside the brain. (March 2023) - Shur, Michael; Akouissi, Outman; Rizzo, Olivier; Colin, Didier J.; Kolinski, John M.; Lacour, Stéphanie P.
Abstract: The brain is an ultra-soft viscoelastic matrix. Sub-kPa hydrogels match the brain's mechanical properties but are challenging to manipulate in an implantable format. We propose a simple fabrication and processing sequence, consisting of de-hydration, patterning, implantation, and re-hydration steps, to deliver brain-like hydrogel implants into the nervous tissue. We monitored in real-time the ultra-soft hydrogel re-swelling kinetics in vivo using microcomputed tomography, achieved by embedding gold nanoparticles inside the hydrogel for contrast enhancement. We found that re-swelling in vivo strongly depends on the implant geometry and water availability at the hydrogel-tissue interface. Buckling of the implant inside the brain occurs when the soft implant is tethered to the cranium. Finite-element and analytical models reveal how the shank geometry, modulus and anchoring govern in vivo buckling. Taken together, these considerations on re-swelling kinetics of hydrogel constructs, implant geometry and soft implant-tissue mechanical interplay can guide the engineering of biomimetic brain implants.